A Metal‐Free Synthesis of N‐Aryl Oxazolidin‐2‐Ones by the One‐Pot Reaction of Carbon Dioxide with N‐Aryl Aziridines. Issue 14 (21st June 2020) - Sonzini, Paolo; Damiano, Caterina; Intrieri, Daniela; Manca, Gabriele; Gallo, Emma
Abstract: The cost‐effective TPPH2 /TBACl‐catalyzed (TPPH2 =dianion of tetraphenyl porphyrin; TBACl=tetrabutyl ammonium chloride) carbon dioxide cycloaddition to N ‐aryl aziridines was successful in synthesizing N ‐aryl oxazolidin‐2‐ones. A catalytic tandem reaction was also developed, in which N ‐aryl aziridines were initially synthesized and then reacted with carbon dioxide without being purified. The procedure occurred with a very high atom economy, molecular nitrogen being the only by‐product of the entire tandem process. In addition, the mechanism of catalytic cycle was investigated by DFT calculations. Abstract :